Experiences and Perceived Self-Efficacy in Distance Learning Among Teachers of Students With Special Educational Needs - Maurer, Jenny; Becker, Angelika; Hilkenmeier, Johanna; Daseking, Monika (Frontiers in Psychology, 2021)
The COVID-19 pandemic has had a great impact on school learning so far, creating a new and potentially stressful situation during school closures for teachers and students. The sudden switch to distance learning might have been especially hard to cope with for students with special educational needs (SEN). Teachers of student with SEN might thus face greater obstacles when establishing and dealing with distance learning. Teachers' self-efficacy (TSE) is a well-known factor for students' academic achievement and motivation. Little is yet known about TSE in distance learning, especially not with students with SEN. The present study aimed to investigate the experiences and the perceived TSE in distance learning of teachers teaching students with SEN at special schools and inclusive schools during the COVID-19 pandemic in Germany during June 2020 and January 2021. N = 96 teachers from both special schools and inclusive schools were involved in the study and were asked to complete a self-report online questionnaire. The study follows an exploratory design to give a first overview of the experiences of teachers of students with SEN and their TSE during the school closures and distance learning. Results showed that no major difference in overall teaching experiences could be found between teachers teaching at special schools or inclusive schools. The identification of difficulties in reading at distance and the support of students with difficulties in reading at distance was perceived by the teachers as most difficult. Difficulties in writing was being rated significantly less easy to identify at distance than difficulties in mathematics. Further, the support of students with difficulties in mathematics was perceived as being significant more challenging than the identification of difficulties in mathematics. TSE in distance learning was rather low, regardless if the teachers taught at a special school or inclusive school in this time period. TSE correlated positively with the perceived goodness of identification of difficulties and support of students with difficulties in reading, writing, and mathematics. Possible reasons and implications are discussed as well as implications of the overall results for distance learning of students with SEN.